Practices and challenges of preservice teachers on flexible learning modality - Codilla Jr., Leo L.; Escote, Jorelle R.; Olavides, Shenna H.; Samosino, Ian S. (Institute of Advanced Engineering and Science, 2025)
This study examined the level of the preservice teachers’ practices in terms of adaptability and time management and the extent of the challenges in terms of internet connectivity and learning environment on flexible learning modality in the post-pandemic time. The study further looked into the relationship between preservice teachers’ practices and their challenges. The study employed a descriptive-correlational approach to comprehensively understand the practices utilized by preservice teachers and the challenges they encounter in adapting to flexible learning modalities. The results reveal that the level of the practices the preservice teachers apply in flexible learning modality is high, and the extent of challenges is also high. Furthermore, the results indicate a significant relationship between the practices and preservice teachers’ challenges in flexible learning. This study contributes to the field of education by providing insights into the adaptability and resourcefulness of preservice teachers navigating flexible learning modalities in the post-pandemic context. Moreover, the findings gave educational institutions and policymakers a glimpse of possible support strategies to improve flexible learning frameworks.